Peran KH Arsyad dalam Penyebaran Agama Islam di Menes Tahun 1916-1948 - Wahyudi, Gandi; Ali , Mohammad; Fauzan, Rikza (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine role KH. Tb Arsyad spread Islam in Menes on 1915-1948. Historical methods used in research include: heuristics (data collection), source criticism, interpretation, and historiography. theory used in research is role theory by Bruce J. Biddle and Edwin J. Thomas. Results of this research conclude KH. Tb Arsyad is one of the Islamic religious from Menes Pandeglang, Banten. He lived in Tegal Menes Village and spread Islam in 1916. During his lifetime KH. Tb Arsyad is known as a man who is sincere, and has extensive knowledge. KH. Tb Arsyad spread Islamic teachings in Menes by using da'wah media by helping KH. Tb Asnawi Caringin. After the eruption of Mount Krakatu in 1838 KH. Tb arsyad finally settled and spread Islamic teachings in Tegal Menes Village, now is Cikedal. KH. Tb Arsyad fosters children and adults through basic recitation such as the introduction tajwid, learning to write Arabic letters of the Al-Qur;an, teaching of obligations that must be carried out as Muslims, as well as establishing an Islamic educational institution, namely Mathla'ul Anwar in 1916 as well as one of the a class V teaching teacher at Madrasa Mathla'ul Anwar in 1916. 1926 M name Mathla'ul Anwar was refined become Mathla'ul Anwar Linahdlatil Ulama (MALNU). His role in the Nahdlatul Ulama organization in 1928 was as one of the First Mustasyar Nahdlatul Ulama in Banten, especially Menes, and not only as a fighter in spreading Islam but also as a fighter in gaining independence.